ARIMAX Modelling of Ron97 Price with Crude Oil Price as an Exogenous Variable in Malaysian - Sarpong-Streetor, R.M.N.Y. (Springer Science and Business Media B.V., 2021)
Malaysiaâs petroleum fuel pricing policy has shuffled between Automatic Adjusted Formula (APM) and Managed Float System (MFS). One major problem in forecasting fuel prices is the use of the structural model. The model uses an input or independent variable, the refined fuel price also known as Mean of Platts Singapore (MOPS). MOPS is published regularly but is sold, which makes it inaccessible to a section of forecasters in Malaysia. In this paper, we suggest an alternative method of forecasting Ron97 price by applying the time series method, Autoregressive Integrated Moving Average with Explanatory Variable (ARIMAX) to model and forecast Ron97 price in Malaysia using publicly available data. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.